Migrant care workers and rehospitalization among older patients discharged from acute care hospitals. Issue 2 (26th February 2014) - Fusco, Sergio; Corsonello, Andrea; Chiatti, Carlos; Fabbietti, Paolo; Salerno, Giovanni; De Bonis, Eugenio; Corica, Francesco; Lattanzio, Fabrizia
<x xml:space="preserve">Abstract</x> Aim The relationship between support at home and rehospitalization has not been extensively studied until now. In particular, little is known about the impact of being assisted by migrant care workers (MCW) and rehospitalization. We aimed at investigating such a relationship in a population of older patients discharged from hospitals. Methods Our series consisted of 506 patients aged 65 years or older consecutively enrolled in a prospective observational study involving 11 acute care medical wards throughout Italy. The outcome of the study was the occurrence of at least one rehospitalization during 1‐year follow up. Information derived from comprehensive geriatric assessment, discharge diagnoses and prescribed drugs were collected during the index hospitalization. Data about formal and informal assistance (spouse, son, other relative, MCW, home nursing) were collected. The relationship between study variables and rehospitalization was assessed using logistic regression. Results Being assisted by MCW was independently associated with the outcome (OR 2.04, 95% CI 1.10–4.37), as were complete dependency (OR 2.49, 95% CI 1.28–5.79) and overall comorbidity (OR 1.23, 95% CI 1.10–1.43). Older age was associated with a lower likelihood of rehospitalization (age 75–84 vs <75 years OR 0.51, 95% CI 0.30–0.92; age ≥85 vs <75 years OR 0.30, 95% CI 0.12–0.65). Conclusions Being assisted by MCW could contribute to an increase in the rate of use of hospital resources for older complex patients. This finding raises the need for educational efforts targeting MCW. Geriatr Gerontol Int 2015; 15: 196–203.